Efficacy and safety of total glucosides of paeony in the treatment of systemic lupus erythematosus: A systematic review and meta-analysis - Gong, Xiaohong; Li, Huan; Guo, Hongtao; Wu, Shangwen; Lu, Chaoqun; Chen, Yiming; Li, Songwei (Frontiers in Pharmacology, 2022)
Background: Total glucosides of paeony (TGP), extracted from the Chinese medicine Paeonia lactiflora Pall., have been proven to be effective in various autoimmune diseases. We aim to systematically evaluate the efficacy and safety of TGP combined with different conventional therapeutic agents in the treatment of systemic lupus erythematosus (SLE). Methods: Eight databases were searched for randomized controlled studies of TGP for SLE. The search time was set from the establishment of the databases to March 2022. The risk of bias was assessed by the Cochrane Evaluation Manual (5.1.0), RevMan 5.3 software was used for meta-analysis, and the certainty of the evidence was assessed by the GRADE methodology. Results: A total of 23 articles were included, including 792 patients overall in the treatment group and 781 patients overall in the control group. The meta-analysis results showed that TGP combined with conventional treatments was superior to the conventional treatments in reducing the SLE disease activity and the incidence of adverse reactions (SMDTGP+GC+CTX = −1.98, 95% Cl = [−2.50, −1.46], p < 0.001; SMDTGP+GC+HCQ = −0.65, 95% Cl = [−1.04, −0.26], p <0.001; SMDTGP+GC+TAC = −0.94, 95% Cl = [−1.53, -0.34], p < 0.05; SMDTGP+GC = −1.00, 95% Cl = [−1.64, −0.36], p < 0.05; and RRTGP+GC+CTX = 0.37, 95% Cl = [0.21, 0.64], p < 0.001). The results also showed that TGP helped improve other outcomes related to SLE disease activity, such as complement proteins (C3 and C4), immunoglobulins (IgA, IgM and, IgG), ESR, CRP, 24 h urine protein, and recurrence rate. In addition, TGP may also be effective in reducing the average daily dosage of glucocorticoids (GCs) and the cumulative dosage of cyclophosphamide (CTX). The certainty of the evidence was assessed as moderate to low. Conclusion: TGP is more effective and safer when used in combination with different conventional therapeutic agents. It helped reduce the disease activity of SLE and the incidence of adverse reactions. However, we should be cautious about these conclusions as the quality of the evidence is poor. Future studies should focus on improving the methodology. High-quality randomized controlled trials (RCTs) will be necessary to provide strong evidence for the efficacy of TGP for SLE. Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO, identifier CRD42021272481